Susceptibility of Wild Canids to SARS-CoV-2 - Stephanie M. Porter; Airn E. Hartwig; Helle Bielefeldt-Ohmann; Angela M. Bosco-Lauth; J. Jeffrey Root (Emerging Infectious Diseases, 2022)
We assessed 2 wild canid species, red foxes (Vulpes vulpes) and coyotes (Canis latrans), for susceptibility to SARS-CoV-2. After experimental inoculation, red foxes became infected and shed infectious virus. Conversely, experimentally challenged coyotes did not become infected; therefore, coyotes are unlikely to be competent hosts for SARS-CoV-2.